Primary Intimal Sarcoma of the Pulmonary Artery in a 25-Year-Old Woman with Dyspnea and Palpitation: A Case Report - Hiroko Onagi (Case Reports in Oncology, 2021)
Intimal sarcoma arising from the tunica intima of both systemic and pulmonary circulations is a rare disorder, whereas intimal sarcoma with chondroblastic osteosarcomatous differentiation (ISCOS) is even rarer. We present the case of a 25-year-old woman with ISCOS of the pulmonary artery (PA) where the patient went through surgical treatment after careful imaging assessment under a rather emergent situation. A 25-year-old Japanese female presented to our hospital with the chief complaints of dyspnea and palpitations on exertion. Upon arrival, she had systolic murmur, moderate tricuspid regurgitation, and possible pulmonary hypertension. A contrast-enhanced chest computed tomography (CT) showed dilatation of the main PA, filled with a hypodense area with calcification adjacent to the right and left PA. The calcified lesions within the tumor were the key findings suggesting osteoid-forming sarcoma, differentiating it from pulmonary embolism. Due to presence of critical symptomatic obliteration of the pulmonary circulation, an emergency surgery was performed. A whitish shiny mass filled the lumens from the main PA to the bilateral main PAs. The tumor was not attached to the surrounding intima, except for a slight attachment to the left interlobar PA, and could be completely removed from the vessel lumen. Based on the pathological findings, it was diagnosed as a primary ISCOS of the PA, which correlated with the findings of the CT, namely intratumoral calcification. Although the diagnosis-making is quite challenging, multidisciplinary collaboration between clinicians, radiologists, and pathologists is crucial for reaching the correct diagnosis.